What managers can do to keep women in engineering - Fernando, Dulini; Cohen, Laurie; Duberley, Joanne (Harvard Business Review, 2018)
Engineering faces a serious gender-based retention problem. Despite all the efforts encouraging women to study engineering, over 40% of highly skilled women who enter the field end up leaving. Much has been written about why women in the field leave, but researchers wanted to better understand what encourages women to stay. In-depth, one-on-one interviews with 34 women engineers in two UK firms found that certain forms of support, such as stretch assignments, personalized feedback, and an inclusive environment, made it easier for these women to succeed in the field.